Computer Applications in Sustainable Forest Management Including Perspectives on Collaboration and Integration - Shao, Guofan; Reynolds, Keith M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
Computer Applications in Sustainable Forest Management presents state-of-the-art computer applications in a variety of specialty areas of forestry, including inventory, remote sensing, information management, modelling and visualization, biometrics, forest and harvest planning, bioeconomics and marketing, and decision science for management. This book emphasizes integration, or collaborative use, of computer technologies across different disciplines through interdisciplinary research and development in North America, China, and Europe. It also offers important new insights on how to continue advancing computational technologies in forest management to better achieve the basic goal of sustainable forest management. Case studies demonstrate integration of, or collaboration among, multiple computer applications for sustainable forest management.
Core technologies -- High-spatial-resolution remote sensing -- Active remote sensing -- Forest information systems -- Road and harvesting planning and operations -- Forest simulation models -- Visualization with spatial data -- Computer-aided decision making -- Bioeconomic and market models -- Synthetic applications -- Digital forestry in the wildland-urban interface -- Linking multiple tools: an american case -- Linking multiple tools: a chinese case -- Conclusions -- From data to sustainable forests.
Keywords: Forestry; Bioinformatics .; Computational biology .; Forestry management; Environmental management; Nature conservation; Application software; Forestry; Computer Appl. in Life Sciences; Forestry Management; Environmental Management; Nature Conservation; Computer Applications